2014
DOI: 10.1186/s13048-014-0093-3
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone improves follicular fluid bone morphogenetic protein-15 and accumulated embryo score of infertility patients with diminished ovarian reserve undergoing in vitro fertilization: a randomized controlled trial

Abstract: ObjectiveTo evaluate the effect of dehydroepiandrosterone (DHEA) on infertility patients with diminished ovarian reserve undergoing in vitro fertilization.MethodsThis is a prospective study. Ninety-five patients with diminished ovarian reserve were included in this study. Of them, 42 patients were randomly allocated to the DHEA group, who received DHEA 75 mg daily for three consecutive menstrual cycles prior to IVF cycles, and 53 patients were allocated to the control group, who entered IVF cycles directly. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 30 publications
6
51
2
Order By: Relevance
“…Several randomized prospective controlled studies investigated the effects of DHEA supplementation but their results were inconsistent. Some researchers obtained the same results as described earlier (34,(38)(39)(40), but the number of oocytes retrieved and the fertilization rate remained inconsistent (38,40,41), whereas others failed to show that DHEA was effective at improving IVF outcomes (40,41). These studies, …”
Section: The Effects Of Dhea Supplementation In Women With Dorsupporting
confidence: 71%
See 1 more Smart Citation
“…Several randomized prospective controlled studies investigated the effects of DHEA supplementation but their results were inconsistent. Some researchers obtained the same results as described earlier (34,(38)(39)(40), but the number of oocytes retrieved and the fertilization rate remained inconsistent (38,40,41), whereas others failed to show that DHEA was effective at improving IVF outcomes (40,41). These studies, …”
Section: The Effects Of Dhea Supplementation In Women With Dorsupporting
confidence: 71%
“…A previous casecontrol study showed that DHEA improved ovarian reserve and that it significantly increased antral follicle counts (AFCs), anti-Müllerian hormone (AMH) levels (32)(33)(34), numbers of fertilized oocytes, normal day 3 embryos, embryos transferred, and the average embryo score per oocyte (35) while significantly decreasing day 3 follicle-stimulating hormone (FSH) (33), fertilized aneuploid embryos (36), and miscarriage rates (37) (all p-values < 0.05). Estradiol (E2) levels tripled according to two studies (12,38) but decreased according to a third (34). Several randomized prospective controlled studies investigated the effects of DHEA supplementation but their results were inconsistent.…”
Section: The Effects Of Dhea Supplementation In Women With Dormentioning
confidence: 99%
“…9a) [17,27]. The other five articles [2, 15,29,31,36] also showed similar results (WMD 0.38, 95 % CI 0.26-0.5, P < 0.0001, I 2 = 0 %; Fig. 9b).…”
Section: Ovarian Reserve Markerssupporting
confidence: 67%
“…Six selfcontrol studies also indicated that DHEA treatment increased the AFC, with no significant heterogeneity observed (WMD 0.4, 95 % CI 0.14-0.66, p = 0.002, I 2 = 24 %, Fig. 10) [15,26,27,29,31,36].…”
Section: Ovarian Reserve Markersmentioning
confidence: 99%
See 1 more Smart Citation